2021
DOI: 10.1016/j.psj.2021.101429
|View full text |Cite
|
Sign up to set email alerts
|

Dietary tributyrin improves reproductive performance, antioxidant capacity, and ovary function of broiler breeders

Abstract: The objective of this experiment was to investigate the influence of dietary tributyrin on reproduction performance and ovary function of broiler breeders with different egg laying rate. Two hundred fifty-six AA broiler breeders (48-wk-old) were allocated to 4 treatment in a 2 × 2 factorial arrangement with the main effects of tributyrin supplementation (0 and 1,000 mg/kg tributyrin [ TRI ]) and 2 egg laying rate levels (average [ AR , 81.01 ± 0.79%] and low [ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 44 publications
0
15
0
Order By: Relevance
“…A previous study reported that hepatic fat accumulation is positively correlated with apoptosis in the ovaries in broiler breeder hens [ 6 ]. Additionally, it has been demonstrated that breeders with lower egg laying rates had higher ovarian-cell apoptosis rates [ 45 ]. Bcl-2 family proteins play important roles in the regulation of cellular apoptosis, among which Bcl-2 is the most representative anti-apoptotic protein, whereas Bax exhibits pro-apoptotic activity [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…A previous study reported that hepatic fat accumulation is positively correlated with apoptosis in the ovaries in broiler breeder hens [ 6 ]. Additionally, it has been demonstrated that breeders with lower egg laying rates had higher ovarian-cell apoptosis rates [ 45 ]. Bcl-2 family proteins play important roles in the regulation of cellular apoptosis, among which Bcl-2 is the most representative anti-apoptotic protein, whereas Bax exhibits pro-apoptotic activity [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Dietary supplementation with tributyrin has been demonstrated to improve animal production performance and disease resistance in monogastrics [ 27 , 28 , 29 ] and ruminants [ 30 ]. Notably, the positive effect of tributyrin may be attributed to the production of butyrate, which can promote the proliferation and differentiation of intestinal mucosal cells and improve nutrient absorption and utilization [ 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Two hundred and forty 26-day-old Hexi dwarf female broilers were randomly allotted into two experimental groups with similar conditions to those under which commercial farm animals were kept before the first day of the trial. After one week of adaptation, the control group (NC) received a basal diet, while the TB group received the same basal diet supplemented with 1 g/kg of dietary tributyrin [ 20 ] (Jinfulai Technology Development Co., Ltd., Harbin, China). All groups consisted of 6 replicates per treatment and 20 chickens in each replicate.…”
Section: Methodsmentioning
confidence: 99%